Consumer Privacy Rights in E-Commerce - Devia Julianda; Irfan Rizky Hutomo; Muhammad Zainuddin (CV. Green Publisher Indonesia, 2026)
The rapid expansion of e-commerce in Indonesia has been fueled by advances in digital technology, leading to a significant increase in the collection and processing of customers' personal data by digital service providers. While electronic transactions offer convenience and efficiency, the risk of consumer privacy violations is equally growing. The misuse of personal data, information leaks, and a lack of transparency in data management by e-commerce platforms are major issues in today's digital ecosystem. A legal study is therefore necessary to understand the extent to which Indonesian regulations protect consumer privacy rights in e-commerce. This study aims to examine Indonesian laws protecting consumers' right to privacy in online transactions and to identify implementation challenges. A normative juridical research methodology is employed, drawing on statutory and doctrinal perspectives. The primary legal sources examined include Law Number 27 of 2022 concerning Personal Data Protection (the PDP Law), Law Number 8 of 1999 concerning Consumer Protection, and other relevant regulations such as Government Regulation Number 71 of 2019 concerning the Implementation of Electronic Systems and Transactions. Secondary legal sources, including scholarly literature, academic publications, and the views of relevant legal experts, are also utilized. This study is expected to offer a more comprehensive understanding of consumer privacy protection in digital transactions and to provide policy recommendations for improving the effectiveness of existing regulations. With robust legal protection in place, it is hoped that consumer privacy rights in e-commerce can be better guaranteed, thereby strengthening public trust in digital transactions.